Brassinolide improves the tolerance of Malus hupehensis to alkaline stress - Sun, Zhijuan; Zou, Yawen; Xie, Cheng; Han, Lei; Zheng, Xiaodong; Tian, Yike; Ma, Changqing; Liu, Xiaoli; Wang, Caihong (Frontiers in Plant Science, 2022)
Malus hupehensis is one of the most widely used apple rootstocks in china but is severely damaged by alkaline soil. Alkaline stress can cause more serious harmful effects on apple plants than salt stress because it also induces high pH stress except for ion toxicity, osmotic stress, and oxidative damage. Brassinolide (BL) plays important roles in plant responses to salt stress. However, its role and function mechanism in apple plants in response to alkaline stress has never been reported. This study showed that applying exogenous 0.2 mg/L BL significantly enhanced the resistance of M. hupehensis seedlings to alkaline stress. The main functional mechanisms were also explored. First, exogenous BL could decrease the rhizosphere pH and promote Ca2+ and Mg2+ absorption by regulating malic acid and citric acid contents and increasing H+ excretion. Second, exogenous BL could alleviate ion toxicity caused by alkaline stress through enhancing Na+ efflux and inhibiting K+ expel and vacuole compartmentalization. Last, exogenous BL could balance osmotic stress by accumulating proline and reduce oxidative damage through increasing the activities of antioxidant enzymes and antioxidants contents. This study provides an important theoretical basis for further analyzing the mechanism of exogenous BL in improving alkaline tolerance of apple plants.